1993
DOI: 10.1055/s-2007-1025217
|View full text |Cite
|
Sign up to set email alerts
|

Welche Therapie erfordert die pränatal diagnostizierte multizystische Nierendysplasie?

Abstract: Multicystic dysplastic kidneys (MCD) were found in 17 of 114 neonates with prenatal diagnosis of urinary tract malformations. Distribution of side and of sex was not different. Contralateral malformations were present in 3 infants. One of them with contralateral renal dysplasia and cardiac malformation died at the age of 4 weeks. All other children so far have a normal renal function. Three neonates presented with a palpable abdominal mass, 2 infants had urinary infections during the first year of life. Two ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Hypertension is a potential complication associated with MCDK [12,13,16,17,19,22,26]. There are only several case reports on hypertension in children with MCDK in the literature [2±4, 11,16,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypertension is a potential complication associated with MCDK [12,13,16,17,19,22,26]. There are only several case reports on hypertension in children with MCDK in the literature [2±4, 11,16,23].…”
Section: Discussionmentioning
confidence: 99%
“…Arterial hypertension is a potential complication of MCDK. The frequency of hypertension in patients with MCDK is considered to be very low but the estimated incidence in several studies varies widely from 0% to 8% [8,13,16,17,22]. In the two largest studies published so far, hypertension has been found only in 6 of 137 and in 4 of 260 patients [19,26] although neither study has focused primarily on blood pressure (BP).…”
Section: Introductionmentioning
confidence: 97%
“…As shown in this study and by others [3] the natural history is mostly a decrease in volume of the aected kidney with occasional total regression and compensatory hypertrophy of the contralateral kidney. Until recently, nephrectomy was recommended [6], whereas nowadays conservative management is almost generally accepted with US follow up [13].…”
Section: Discussionmentioning
confidence: 99%
“…There are only several case reports on hypertension in children with MCDK in the literature [60][61][62][63][64][65][66] but systematic investigations of BP in patients with MCDK are rare and based on clinic BP measurements only. The frequency of hypertension in children with MCDK in these studies has been shown to be relatively low with the prevalence ranging between 0 -8% [4,58,59,64,[67][68][69][70][71][72]. However Emmert and Webb [73,74] suggested in their papers that the risk of hypertension secondary to MCDK is underestimated and many children therefore receive suboptimal follow-up.…”
Section: Hypertension In Children With Multi-cystic Dysplastic Kidneymentioning
confidence: 94%